Thermomechanical Behavior of Polymer Composites Based on Edge-Selectively Functionalized Graphene Nanosheets - Nam, Ki-Ho; Cho, Jaehyun; Yeo, Hyeonuk (MDPI, 2018)
In this study, we demonstrate an effective approach based on a simple processing method to improve the thermomechanical properties of graphene polymer composites (GPCs). Edge-selectively functionalized graphene (EFG) was successfully obtained through simple ball milling of natural graphite in the presence of dry ice, which acted as the source of carboxyl functional groups that were attached to the peripheral basal plane of graphene. The resultant EFG is highly dispersible in various organic solvents and contributes to improving their physical properties because of its unique characteristics. Pyromellitic dianhydride (PMDA) and 4,4'-oxydianiline (ODA) were used as monomers for constructing the polyimide (PI) backbone, after which PI/EFG composites were prepared by in situ polymerization. A stepwise thermal imidization method was used to prepare the PI films for comparison purposes. The PI/EFG composite films were found to exhibit reinforced thermal and thermo-mechanical properties compared to neat PI owing to the interaction between the EFG and PI matrix.
Keywords: COVALENT; OXIDE; NANOCOMPOSITES; EXFOLIATION; DISPERSION; GRAPHITE; NETWORK; BARRIER